Escapism and Video Game Addiction in Adolescents - K.S. Shalaginova; E.V. Dekina; D.A. Klochneva (Moscow State University of Psychology and Education, 2023)
The article analyzes the problem of the formation of video game addiction in adolescents with a tendency to escapism. Escapism is considered as a predictor of video game addiction in adolescents in the information society, the motivation to escape from the fear of a trivial life and everyday difficulties in the virtual worlds of cyberspace. The study involved students of the Agricultural College of the city of Tula from 16 to 18 years old in the amount of 98 people. The purpose of the article is to provide a psychological and pedagogical analysis of the personality characteristics of adolescents that influence the formation of an addictive behavior model in relation to computer games. To achieve the goal of the study, the following psychological tools were used: the Thomas A. Tucker test (adapted by I.A. Konygina), the General Scale for Problematic Internet Use-3 (GPIUS-3) (A.A. Gerasimov, A.B. Kholmogorova), test "Scale for assessing the level of reactive and personal anxiety" Ch.D. Spielberg (adapted by Yu.L. Khanin), a questionnaire to identify the approximate time spent by teenagers on video game content, the test "Methodology for measuring the level of escapism" (T.N. Savchenko, O.I. Teslavskaya, E.V. Belovol, A.A. Kardapoltseva). The conducted study allows us to conclude that the parameter "escapism" is significantly correlated with the parameters "anxiety", "the degree of formation of a video game addict", as well as the time spent by a teenager on gaming content. There is a significant correlation of escapism with the parameter "negative consequences" from a computer game. It is worth noting the absence of a significant correlation between “flight” and “preference for online communication”. The results of the study are considered by the authors in the context of solving the problems of preventive work with adolescents implementing an escapist strategy of behavior, preventing the development of video game addiction. The obtained empirical data confirm the expediency of taking into account the personality characteristics of adolescents in the psychological and pedagogical prevention of video game addiction in adolescents